2019
DOI: 10.1038/s41433-019-0696-4
|View full text |Cite
|
Sign up to set email alerts
|

No impact of nasal septoplasty on the outcome of endoscopic dacryocystorhinostomy

Abstract: Objective To compare the outcomes of combined endoscopic dacryocystorhinostomy (endoDCR) with nasal septoplasty for deviation of the nasal septum to endoDCR alone in cases of nasolacrimal duct obstruction (NLDO). Methods A retrospective cohort study that included 107 consecutive patients with NLDO, who underwent endoDCR with or without concomitant nasal septoplasty in our institution between October 2009 and October 2017. Results A total of 117 operations were performed (107 patients, 80.4% females; mean age ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…The reported rate of concomitant EDCR and septoplasty ranges from 11.9 to 57% [11,[24][25][26][27][28][29][30][31]. Per the literature, 39.7% of our cases were managed with a combined procedure.…”
Section: Discussionmentioning
confidence: 79%
“…The reported rate of concomitant EDCR and septoplasty ranges from 11.9 to 57% [11,[24][25][26][27][28][29][30][31]. Per the literature, 39.7% of our cases were managed with a combined procedure.…”
Section: Discussionmentioning
confidence: 79%
“…Tsirbas and Wormald reported a rate of approximately 46% of patients requiring a septoplasty, stating that in order to create a larger ostium, better access is needed, but an analysis on its influence on the outcome was not performed [9]. Koval, et al stated that septoplasty had no statistically significant impact on the outcome of en-DCR, despite raw data analysis showing a decrease in en-DCR functional success when septoplasty was concurrently performed [20]. In contrast, even though differences between both groups also did not achieve statistical significance in our study, the en-DCR + septoplasty group achieved better results regarding a successful outcome when compared to the en-DCR alone group (93.3% vs. 87.1% respectively).…”
Section: Resultsmentioning
confidence: 99%
“…These procedures can include a variety of methods, with septoplasty being 1 of the most common adjunctive techniques. Rates of concurrent septoplasty vary, ranging between 12% and 47% 36–39 . When evaluating bilateral DCR vs unilateral DCR specifically, septoplasty was performed with greater frequency (57% vs 17%) 40 …”
Section: Resultsmentioning
confidence: 99%
“…32,34,41 Chan et al 42 reported that over a 5-year period, 67% of the failures of the external DCRs in their series were attributed to the presence of a nasal septal deviation, with a 100% success rate in these cases following revision DCR surgery that also included a septoplasty. When comparing endoscopic DCR along with septoplasty to endoscopic DCR alone, Koval et al 39 found similar anatomic and functional success rates with no complications associated with the septoplasty portion of the procedure.…”
Section: Concurrent Septoplastymentioning
confidence: 99%
See 1 more Smart Citation